Achieving Software Release Management and Continuous Integration using Maven, Jenkins and Artifactory - Shahbaz Ali Syed; Tariq Rahim Soomro (International Journal of Experiential Learning & Case Studies, 2018)
It is often required that the developers working on a single module or software project, while working from remote locations. Scenarios like that increase complexity and challenge to manage releases and to merge their daily work in a single artifact. For component based development, developers are responsible for the merging their own work with others and to make sure the integrations went smooth with no error and problems. Sometimes it’s hard to do this job because of the large size of team members, big project size or geographically separated teams.  Through Continuous integration this whole process becomes lot easier because all the validations and verifications will be done by an automated job.  This job will check for the changes in the project code and whenever a change happens it will run the build process automatically, which detects errors and problems with the code and also notifies the concerned team member who is responsible for this error. This study introduces an approach to setup a Continuous Integrations techniques in a project using open source tools like Maven, Jenkins and Artifactory.